2019
DOI: 10.1088/1757-899x/693/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficiency of lightweight concrete modified with additives based on nanostructures

Abstract: The paper presents the results of studies on assessing the effectiveness of the modification of lightweight concrete with nanostructures. The results of these experimental studies show that the introduction of additives based on nanostructures, such as dispersions of carbon nanotubes and silica nanoparticles, improves the physical-mechanical characteristics of lightweight foam concrete (LWFC), even at low additive concentrations. As a result of chemical and physical interactions, nanosilica (NS) accelerates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Vaganov et al [54] studied how to achieve high performance concrete, and to investigate if utilizing other admixtures, such as carbon nanotubes (CNT), and possibility to localize alkali silica reactions to improve the durability of foam concrete. Sldozian et al [55] found that when (0.0004-0.0012 percent) CNTs (Taunit 24) and NS are combined in modest dosages are added to lightweight concrete with granulated foamed glass, compressive and flexural strength is increased by (up to 68 percent) and (up to 34 percent), respectively, as well as decrease water absorption by (8%). Afzali Naniz and Mazloom [56] found that the combined of using of silica fume and colloidal nano silica (CS) significantly improved the selfcompacting lightweight concrete characteristics than when used only CS.…”
Section: Nano Materialsmentioning
confidence: 99%
“…Vaganov et al [54] studied how to achieve high performance concrete, and to investigate if utilizing other admixtures, such as carbon nanotubes (CNT), and possibility to localize alkali silica reactions to improve the durability of foam concrete. Sldozian et al [55] found that when (0.0004-0.0012 percent) CNTs (Taunit 24) and NS are combined in modest dosages are added to lightweight concrete with granulated foamed glass, compressive and flexural strength is increased by (up to 68 percent) and (up to 34 percent), respectively, as well as decrease water absorption by (8%). Afzali Naniz and Mazloom [56] found that the combined of using of silica fume and colloidal nano silica (CS) significantly improved the selfcompacting lightweight concrete characteristics than when used only CS.…”
Section: Nano Materialsmentioning
confidence: 99%
“…[17][18][19]. The use of different nano-modi ers, including those containing carbon, to modify composite materials holds promise because their introduction enhances the physicomechanical properties at low additive dosages and enables directionally controlled modi cation of the material's structure [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The most typical way to generate an aqueous suspension using pre-synthesized nanostructures is to process them further in the rst form before the procedure of entry into the composite structure (for example, by processing a dry combination of components). Signi cant challenges in introducing a nano-modi ed and its uniform distribution are reduced to the utmost extent when utilizing the second method [23][24][25][26]. The article's consideration [27,28] on the nanomodi cation of construction composites document favorable structural changes, for instance, the ability of carbon nano-additives to allow much higher values of physicomechanical characteristics In comparison to the unmodi ed samples, the nanomodi ed samples developed large value of calcium hydrosilicates and a low porosity structure, which allowed for these modi cations to occur.…”
Section: Introductionmentioning
confidence: 99%